Development a Fable Book on Conflict Resolution from Bullying to Stimulate the Early Children’s Moral Development - Puspita, Yanti; Atikah, Cucu; Fadlullah, Fadlullah (Lectura : Jurnal Pendidikan, 2024)
Every individual is entitled to education, protection, and respect regardless of race, religion, gender, group, or social status. Bullying in schools violated the right to a safe and comfortable learning environment. Human Rights, which were inherent from birth, could not be taken away. This research resulted in a fable book that showed how negotiation could resolve conflicts and prevent bullying among early children in kindergarten. The study aimed to analyze and describe the feasibility of the fable book in stimulating the moral development of young children. The research methodology used was R&D with a 4D model, consisting of Define, Design, Develop, and Disseminate. The steps in creating the fable book were: 1) Define: analyzed the needs for the fable book medium; 2) Design: created a storyline (storyboard) and designed the necessary elements; 3) Develop: the process of creating the medium; 4) Disseminate: conducted a small-scale trial with 8 students at TK Khoiru Banisaderi. Data collection in this study used interview, unstructured observation, documentation and expert validation questionnaire. Product feasibility validation was conducted by media experts, content experts, and through small group trials at TK Khoiru Banisaderi. The validation results were: 90% from media experts, 92.5% from content experts, and 91% based on students’ responses. Therefore, the book was considered suitable as a medium to stimulate the moral development of young children.